Implementation of the Waterfall Method in the Design of a Website-Based Mail Filing System - Rohman, Auliya’ur; Syarif Hidaytullah, Athia; Rohman, MGhofar (Generation Journal, 2022)
The use of information technology and computers has become a necessity in daily work, both in private and public agencies, especially in terms of service to the community, the use of information technology is certainly very supportive of existing activities. One of the activities at the Department of Population and Civil Registration is the large number of incoming and outgoing letters, this causes problems in archiving, both incoming and outgoing letters, so to overcome this a website-based archive system for incoming and outgoing mail is built. This system was built using the waterfall method. The test results on the archive of incoming and outgoing letters based on this website indicate that this application has been running well, this can be seen in the results of the black box testing which shows that the application is running as expected, and makes it easier for employees to carry out their duties of archiving incoming and outgoing mail.